Genome-Wide Identification and Characterization of Trehalose-6-Phosphate Synthase/Phosphatases Gene Family in Petunia and Their Expression Profiling Under Abiotic Stresses - Renwei Huang; Daofeng Liu; Gonzalo H. Villarino; Neil S. Mattson (Horticulturae, 2025)
Trehalose is a nonreducing disaccharide critical for cellular integrity and stress adaptation in plants, and its synthesis relies on trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP). Despite their established roles in abiotic stress responses across model plants, these gene families remain underexplored in ornamental species like Petunia hybrida. Here, TPS and TPP genes in two wild petunia progenitors, P. axillaris and P. inflata, underwent a genome-wide analysis, with 10 TPS and 8–9 TPP genes being identified in each species. According to phylogenetic analysis, petunia TPS proteins cluster into two clades, while TPP proteins were classified into three clades, showing closer evolutionary ties to tomato homologs. Cis-acting elements profiling identified hormone- and stress-responsive regulatory elements (e.g., ABRE, TC-rich repeats). Expression analysis under drought, heat, and salt stress revealed dynamic temporal regulation. For instance, PaTPS4/PaTPS9 were early responders (peak at 6 h) under drought and salt stress, while PaTPS8 exhibited sustained upregulation during salt treatment. Heat stress uniquely suppressed PaTPS1,2 and PaTPP1, contrasting with broad upregulation of other members. Notably, PaTPP3 displayed delayed induction under heat. These findings underscore the functional diversity within TPS/TPP families, with specific members governing stress-specific responses. This study provides a foundational resource for leveraging these genes to enhance stress resilience and ornamental value in petunia.